Republic of Azerbaijan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
The first paper is on the oil boom in Azerbaijan, which presents a unique opportunity to speed up the development agenda, but at the same time poses challenges to the management of macroeconomic policy. A new fiscal framework to sustain macroeconomic stability and achieve fiscal sustainability is required. The second paper is on Azerbaijan's managed exchange rate policy and the need for an orderly and durable transition to more flexible exchange rate arrangements that can mitigate risks. Even if greater flexibility is not introduced in the short term, improved monetary policy framework needs to be put in place.